Analysis of Consumer Perception of Fairness Cream in Delhi and NCR: Understanding the factors influencing consumer perception of fairness cream in Delhi and NCR (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Skin-lightening or ‘fairness’ creams are big business in India, an over 200 million industry that comprises the largest segment of the country's skin cream market.. Fairness cream is an article which is found in every home today. Even when we are watching television and advertisements come in between the show, at least one advertisement is that of a fairness cream. With so many brands doing the rounds in the market, people even have a variety in choosing which cream they want. The situation is such that we have fairness creams for every age, every skin-type, every weather and it goes for both the sexes. With the fairness cream for men also out in the market, even the males are openly using them now. And, girls' demand for make-up and to look fair is well known since ages. All have their own ways by which they maintain the fair complexion of their skin. So, no doubt that fairness creams sells like hot cakes even today. This paper is an attempt to find and analyze the factors affecting the perception of fairness creams in Delhi and NCR.